Evaluation and Mentorship for Health Cadres in the Implementation of Breastfeeding Support Groups - Susilawati, Susilawati; Arifin, Rani Fitriani; Suherman, Reni (Universitas Padjadjaran, 2024)
WHO recommends that infants are only breastfed until the age of 6 months and given complementary foods (MP-ASI) from the age of 6 months and continue to provide breast milk until 2 years old. Health education conducted by cadres is an effort to increase the knowledge of mothers who support successful breastfeeding and decision making in exclusive breastfeeding. This community service activity aims to evaluate and improve cadre assistance in meeting the exclusive breastfeeding target in 2022. The form of activities in this community service consists of the KP-ASI evaluation method, which is carried out through the method of assessing lactation knowledge in the form of lectures and assistance to breastfeeding mothers and Focus Group Discussion (FGD). This activity was carried out with One Group Pre-Test Post-Test Design. The sample was 18 respondents who used purposive random sampling, data collection using questionnaires, and data analysis using the Wilcoxon test. The results showed that there was an effect of health counseling on the knowledge and enthusiasm of cadres in the Karang Tengah Health Center working area with a p-value <0.05. The conclusion is that evaluation and assistance to cadres can effectively increase the knowledge of health cadres in an effort to encourage the success of exclusive breastfeeding for breastfeeding mothers. Keywords: Exclusive breastfeeding, breastfeeding support group, cadre, breastfeeding mother.